Pengaruh Literasi Keuangan Terhadap Inklusi Keuangan Rumah Tangga Dengan Jaringan Sosial (Network) Sebagai Variabel Moderating - Isna Samrotul Fuadah; Aniek Hindrayani; Salman Alfarisy Totalia (Jurnal Pendidikan Ekonomi (JUPE), 2023)
The research was conducted aiming to determine the effect of financial literacy on household financial inclusion with social networks as a moderating variable for the poor in Blora Regency. This research is a quantitative descriptive research where the research subjects are the poor people of Blora Regency, amounting to 391 respondents. Sampling was carried out using probability sampling with stratified random sampling technique. The process of collecting data is carried out by means of a questionnaire or questionnaire which is distributed to every house that has received a lottery number as a sample. The validity test technique uses the pearson product moment correlation formula. Data analysis used is hierarchical regression using Moderated Regression Analysis (MRA). The research results obtained include. First, financial literacy has a positive and significant effect on the financial inclusion of poor households in Blora Regency. Second, social networks have a positive and significant impact on the financial inclusion of poor households in Blora Regency. Third, social networks strengthen the relationship between financial literacy and the financial inclusion of poor households in Blora Regency.